2004
DOI: 10.3171/jns.2004.101.1.0108
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation geometry and the presence of cerebral artery aneurysms

Abstract: The bifurcation beyond the circle of Willis (that is, the MCA) closely approximated optimality principles, whereas the bifurcations within the circle of Willis (that is, the distal ICA and BA) did not. This indicates that the confluence of hemodynamic forces plays an important role in the distribution of work at bifurcations within the circle of Willis. In addition, the observed branch angles were predictors for the presence of aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 16 publications
8
120
1
5
Order By: Relevance
“…Hemodynamic stress at arterial bifurcations are believed to contribute to aneurysm development (Ingebrigtsen et al 2004). However, it is largely unknown why only some adults develop aneurysms at bifurcations and most do not.…”
Section: Pathology Epidemiology and Etiologymentioning
confidence: 99%
“…Hemodynamic stress at arterial bifurcations are believed to contribute to aneurysm development (Ingebrigtsen et al 2004). However, it is largely unknown why only some adults develop aneurysms at bifurcations and most do not.…”
Section: Pathology Epidemiology and Etiologymentioning
confidence: 99%
“…The present study highlights the five different branching patterns of the basilar artery studied in 170 human cadaveric brains. Various branching patterns in the termination of the artery subjects it to abnormal flow and leads to atherosclerotic changes and aneurysms (6,9). These variations may complicate surgery at the basilar tip at the clivus (4).…”
Section: Pentafurcation Of Basilar Arterymentioning
confidence: 99%
“…1,4,17 Indeed, it has been suggested that a particular bifurcation phenotype may be directly linked to intracranial aneurysms (IAs). 11 An optimal arrangement of branching and bifurcation sites in the cerebral vasculature is essential to preserve minimum energy expenditure along the network by maintaining constant wall shear stress (WSS) across daughter and parent vessels. 11,25 This vascular optimality principle has been shown to generally apply to the cerebral circulation 11,19,20 and implies a relative optimal bifurcation angle depending on the relative sizes of the daughter branches.…”
Section: ©Aans 2014mentioning
confidence: 99%